Using the LBB Method for the Assessments of Seven Fish Stocks From the Yangtze Estuary and Its Adjacent Waters - Wang, Yuanchao; Liang, Cui; Xian, Weiwei; Wang, Yibang (Frontiers in Marine Science, 2021)
The status of fishery resources in the Yangtze estuary and its adjacent waters is still unclear for the effective implementation of fishery management strategies. To help address this gap, a new method especially for data-limited fish stocks (LBB) was applied to assess seven commercially and ecotrophically important fish stocks. Fish specimens were collected in the estuary by bottom trawling quarterly from May 2018 to February 2019. Two historical datasets were collected with the same method in the same area for Indian perch (Jaydia lineata) and sickle pomfret (Pampus echinogaster). To explore the growth features and resilience of fish stocks, auximetric plots and growth performance indices (Φ′) were used. Results showed that common hairfin anchovy (Setipinna tenuifilis) in 2018 and Indian perch in 2018 showed a healthy stock biomass status with complete length structures under a sustainable fishing pressure. The others were outside of safe biological limits or overfished. The Lmean/Lopt < 0.9 in six (67%) of nine LBB models for seven fish stocks suggested that most of the stocks were truncated in length structures. This contribution provides the main fishery reference points regarding stock status that can inform managers and form the basis for various management strategies.